Gambaran Tingkat Kecemasan Ibu Bersalin Pada Masa Pandemic Covid-19 Di RSIA ROSIVA Medan - Hasibuan, Bungaria; Simatupang, Lenny Lusia (STIKes Murni Teguh, 2025)
The labor period is a vulnerable period for psychological disorders in mothers, especially during the Covid-19 pandemic. This situation can cause psychological disorders in mothers in labor where most mothers in labor feel anxious and afraid to undergo examinations and give birth to the hospital because they are afraid of contracting the Covid-19 virus. The purpose of this study was to determine the level of anxiety of mothers in labor during the Covid-19 pandemic. This research method is quantitative with a descriptive design. The study was conducted at Rosiva Medan. The population was 68 people and the total sampling technique was used. The analysis was carried out univariately which is presented in a frequency distribution table. The results of this study indicate that the characteristics of mothers in labor are aged 20-35 years (82.4%), high school education (45.6%), housewives (55.9%), in scundipara parity (50.0%). The anxiety felt by mothers in labor is moderate anxiety (57.4%), experiencing severe anxiety (38.2%), and experiencing mild anxiety (4.4%). It can be concluded that pregnant women experience anxiety about giving birth during the Covid-19 pandemic. It is recommended that health workers (doctors and nurses) at Rosiva provide pharmacological and non-pharmacological therapy to birthing mothers who feel anxious during the birthing process during the Covid-19 pandemic so that their feelings of anxiety can be reduced or disappeared completely so that mothers are more comfortable during the birthing process. It is recommended for future researchers to add non-pharmacological intervention variables to reduce anxiety during childbirth.